2005
DOI: 10.1103/physreve.71.031602
|View full text |Cite
|
Sign up to set email alerts
|

Side-branch growth in two-dimensional dendrites. I. Experiments

Abstract: The dynamics of growth of dendrites' side branches is investigated experimentally during the crystallization of solutions of ammonium bromide in a quasi-two-dimensional cell. Two regimes are observed. At small values of the Peclet number a self-affine fractal forms. In this regime it is known that the mean lateral front grows as t 0.5 . Here the length of each individual branch is shown to grow ͑before being screened off͒ with a power-law behavior t ␣ n . The value of the exponent ␣ n ͑0.5ഛ ␣ n ഛ 1͒ is dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…33 We have shown that, as long as sidebranching is frequent enough for competition among branches to occur, the exact choice of the input parameters N and DN has little influence on the final selected spacings. 15 One limitation of the current implementation is that it does not describe the lateral movement of dendrites.…”
Section: Dendritic Needle Network Modelmentioning
confidence: 90%
“…33 We have shown that, as long as sidebranching is frequent enough for competition among branches to occur, the exact choice of the input parameters N and DN has little influence on the final selected spacings. 15 One limitation of the current implementation is that it does not describe the lateral movement of dendrites.…”
Section: Dendritic Needle Network Modelmentioning
confidence: 90%
“…Other experiments with more rapid transients have seen large sets of sidebranches generated [23,24,25,26]. We also saw no evidence of any transition to doublons, as has been observed in xenon dendrites [27,28].…”
Section: Response To Transientsmentioning
confidence: 50%
“…However, quantitative predictions of those properties remain scarce for alloys. Atomistic [33] -by a network of thin needle crystals that interact through the solute field, as illustrated in (b). The growth dynamics of each individual needle branch is obtained by combining two independent conditions at two distinct length scales: (c) a solute conservation equation at a length scale much larger than the needle tip radius q but much smaller than the diffusion length D=V, and (d) a solvability condition at the scale of the needle tip radius q [138].…”
Section: Discussionmentioning
confidence: 98%